PENGARUH EKUITAS MEREK TERHADAP PROSES PENGAMBILAN KEPUTUSAN PEMBELIAN MOTOR HONDA BEAT DI DEALER GARUDA MOTOR I KECAMATAN GAMBIRAN KABUPATEN BANYUWANGI - Wardhatul Firdananda Hariyanto; Sutrisno Djaja; Sukidin Sukidin (Economic Education, University of Jember, 2017)
This study was conducted to determine the significant effect of brand equity on consumer decision to buy Honda Beat in Gambiran Banyuwangi. The method of determining the location of research using the method of purposive area is at the dealer Garuda Motor I located on Pb. Sudirman Street 44, Jajag, Gambiran, District Banyuwangi. The number of respondents in this study were many as 75 respondents. Data collection methods used consisted of methods: questionnaires, documents, and interviews. Data analysis used is descriptive analysis and inferential/statistic analysis that is by using simple regression line analysis, regression line variance analysis, F test, regression line effectivity, and Standard Error Of Estimate. The result of the research shows that there is significant influence of brand equity on the process of purchasing decision of Honda Beat at Garuda Motor I dealer in Gambiran of Banyuwangi with Fcount = 308,307> Ftable = 3,972 with significance level F = 0,000 <a = 0,05. While the contribution of brand equity to the process of making purchasing decisions Honda Beat gi that is equal to 80,9%, while the rest is 19,1% influenced by other independent variables that are not examined in this study such as location, price level, discounts, and others.